The value of public sector risk management: An empirical assessment of Ghana - Yusheng Kong; Peter Yao Lartey; Fatoumata Binta Maci Bah; Nirmalya B. Biswas (Administrative Sciences, 2018)
This study investigates risk management practices in public entities in the Ghana. We relied on the popular framework designed by the Committee of Sponsoring Organizations of the Treadway Commission-COSO, to advocate for possible ways to minimize the occurrence and effects of risk in public organizations. The internal control elements used include: control environment, commitment to ethics, segregation of duties, review and information and communication. These constitute the explanatory variables used in performing multivariate data analysis to determine the dimensionality of the data set and possible outcomes. The exploratory research followed a quantitative approach using the survey method and a structured equation model. We established that, due to globalization and increases in the scale of operations, it is practically impossible for management through the help of auditors and those in charge of governance to validate the entire operations of the public sector to ensure strict compliance to internal control principles, in order to minimize the detrimental impacts of risk. However, an alternative sustainability depends on the prominence of quality financial reporting, compliance, commitment to ethical values and consistency in pursuit of the strategic and operational objectives based on good corporate governance. On the other hand, the implications of risks should be embedded in the minds of public servants as part of the organizational culture that will complement existing tools and techniques of internal control.
Keywords: 350; public sector; Committee of Sponsoring Organizations of the Treadway Commission (COSO– Enterprise Risk Management); risks assessment; control environment